Multiple Applications, Competing Mechanisms, and Market Power - James Albrecht; Xiaoming Cai; Pieter A. Gautier; Susan Vroman (Center for Economic Studies and ifo Institute (CESifo), 2019)
We consider a labor market with search frictions in which workers make multiple applications and firms can post and commit to general mechanisms that may be conditioned both on the number of applications received and on the number of offers received by its candidate. When the contract space includes application fees, there exists a continuum of equilibria of which only one is socially efficient. In the inefficient equilibria, firms have market power that arises from the fact that the value of a worker's application portfolio depends on what other firms offer, which allows individual firms to free ride and offer workers less than their marginal contribution. Finally, by allowing for general mechanisms, we are able to examine the sources of inefficiency in the multiple applications literature.
Keywords: C78; D44; D83; 330; multiple applications; directed search; competing mechanisms; efficiency; market power